El trabajo comunitario como forma de organización de la fabricación eficiente en los muebles para el hogar en cooperativa “Los Chapulos” de la parroquia San Camilo del cantón Quevedo, año 2015 - Gomezcoello Chalacán, Juliana Karina (2015)
This research dealt with the community service organization as efficient manufacturing in home furniture cooperative "Los Chapulos" Parroquia San Camilo Quevedo Canton, 2015, which took place approximately 180 days , time in which it was possible to meet the overall objective: Evaluate community work in the form of organization in manufacturing home furnishings; and their specific objectives: 1) Develop a diagnosis in community work as a form of organization of the manufacture of furniture for the home, 2) Identify the functional organizations in manufacturing home furnishings, 3) Analyze and community work form of organization in manufacturing home furnishings. The hypothesis is checked when craftsmen cabinetmakers are organized and leave the empirical work. The results of this research objectives resulted in preparing the proposal to design a model of organization for the benefit of manufacturers of wood furniture cooperative "Los Chapulos" sharing the same quality and efficient techniques to delivery of the final product; it will reduce costs when buying wholesale raw materials; This management is performed by the president of the association for the raw material more affordable utilities which let teachers cabinetmakers partners and improve their quality of life, and will benefit customers because the products are with lower prices than the market. Without derogating from the application of values and laws attached to this research provided the necessary tools to describe the findings and recommendations of this research work.